MICROFINANCE AND POVERTY REDUCTION IN NIGERIA: EVIDENCE FROM LOKOJA, KOGI STATE - Enesi Alex, Godwin; Mathew Rotimi, Ekundayo; Olamide Olaoluwa, Babatunde (African Journal of Social and Behavioural Sciences, 2026)
This study investigates the impact of microfinance on poverty reduction in Lokoja, Kogi State, Nigeria, focusing on how microfinance services influence income generation and job creation among beneficiaries. Data were collected from 370 microfinance clients using structured questionnaires and analyzed through descriptive statistics, correlation, and regression analysis. The results indicate that microfinance services significantly enhance poverty reduction primarily through income generation, while job creation was not statistically significant. The findings highlight that access to loans, savings, and financial training improves beneficiaries’ financial autonomy and household welfare. Challenges such as high interest rates, rigid repayment terms, and limited financial literacy constrain the effectiveness of microfinance. Based on these results, the study recommends strengthening financial literacy programs and improving loan accessibility to maximize the poverty-alleviation potential of microfinance services.